Effect of impeller blade trimming on the performance of a 5.5:1 pressure ratio centrifugal compressor. (September 2014) - Swain, Daniel; Engeda, Abraham
Centrifugal compressor blade trimming can be used for the purpose of changing the performance characteristics of an impeller or allowing a single impeller design to be used for a range of operating conditions. There are different methods of impeller blade trimming that may be employed to change the impeller flow rate, the pressure ratio, or both. In this study, computational fluid dynamics is used to model the effects of two different methods of blade trimming on a single centrifugal compressor design. Impeller performance characteristics and analysis of the flow field are presented for a series of trims. Trimming the passage area from inlet to outlet along the meridional length reduced the flow rate of the impeller and narrowed the effective operating range. The head coefficient and efficiency relative to the choked flow coefficient remained unchanged as the passage area is reduced; however, the flow rate is reduced by a greater amount than the inlet area is reduced. Trimming the impeller blades by shifting the shroud profile in the axial direction caused the head coefficient to be reduced while maintaining a constant flow coefficient. This method of trimming is limited by choking in the radial portion of the passage, and the head coefficient for the impeller studied was able to be reduced by up to 15% before further trimming limited the choked flow rate.